2022
DOI: 10.1145/3570618
|View full text |Cite
|
Sign up to set email alerts
|

The Online Knapsack Problem with Departures

Abstract: The online knapsack problem is a classic online resource allocation problem in networking and operations research. Its basic version studies how to pack online arriving items of different sizes and values into a capacity-limited knapsack. In this paper, we study a general version that includes item departures, while also considering multiple knapsacks and multi-dimensional item sizes. We design a threshold-based online algorithm and prove that the algorithm can a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The online knapsack problem and its variants have been extensively studied in the literature [26,31,27,25,34,35]. Nearly all online algorithms in this stream of works are based on a similar idea that estimates the price of admitting one item using a function of the knapsack utilization and admits the item if item value is larger than the estimated price.…”
Section: The Significance Of the Theoretical Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The online knapsack problem and its variants have been extensively studied in the literature [26,31,27,25,34,35]. Nearly all online algorithms in this stream of works are based on a similar idea that estimates the price of admitting one item using a function of the knapsack utilization and admits the item if item value is larger than the estimated price.…”
Section: The Significance Of the Theoretical Resultsmentioning
confidence: 99%
“…This paper designs an order-optimal online algorithm for the most general integral setting. Compared to the other two works with optimal CRs (i.e., [26] and [25]), this work makes additional technical contributions in design and analysis of the algorithm in the general setting. In particular, we extend the analysis of the fractional admission in [26] to integral admission by considering two classes of instances and analyzing their corresponding worst-case ratios using different approaches (see Section 4.2 and 4.3).…”
Section: The Significance Of the Theoretical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, they suggested that the optimal allocation and pricing rules are threshold policies, which offer a uniform price to incoming buyers and the buyers either accept or reject the offer. Furthermore, various computation algorithms for DSKP have been developed to implement allocation policies in practical scenarios (Zhou, Chakrabarty, and Lukose 2008;Han, Kawase, and Makino 2015;Im et al 2021;Sun et al 2022). They focused on online algorithms to allocate resources in response to changing demands and constraints.…”
Section: Related Work Dynamic Stochastic Knapsack Problemmentioning
confidence: 99%